Preparation of Cu2Se thin films by vacuum evaporation and hot-pressing. (March 2021) - Hua, Xiaodong; Li, Jiahui; Liu, Hao; Zhang, Chaoqun; Han, Yu; Gao, Fei; Hodes, Gary; Wang, Pengwei; Yang, Zhou; Liu, Shengzhong (Frank)
Abstract: A method using vacuum evaporation and hot-pressing to prepare Cu2 Se thin films on Cu substrates is developed. The effects of the heating temperature, heating time, and pressure on the crystallinities of the Cu2 Se thin films were studied. The structure, morphology, and composition properties of the Cu2 Se thin films were characterized by the X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The results showed that the crystallinities of the Cu2 Se thin films improved as the heating temperature was increased from 200 °C to 280 °C. A low pressure of 2 MPa and a short time of 5 min were sufficient to obtain highly crystalline Cu2 Se thin films at 280 °C. The fabricated Cu2 Se/Cu structure could directly convert heat to electricity with a thermoelectric potential of 12.6 mV at 400 K and 17.8 mV at 500 K. Compared with conventional hot-pressing of bulk materials, this method requires lower temperatures and smaller pressures. Graphical abstract: Image 1 Highlights: Cu2 Se thin films were prepared by vacuum evaporation and hot-pressing. Effect of hot-pressing condition on crystallinities of Cu2 Se films was studied. This method requires lower temperature (280 °C) and smaller pressure (2 MPa). The fabricated Cu2 Se/Cu structure could directly convert heat to electricity.